Financování ekologických investic pomocí strukturálních fondů EU - Cejnková, Ivana (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Tato diplomová práce se zaměřuje na financování ekologických investic, respektive alternativních zdrojů energie, především tedy financování fotovoltaických elektráren. V části se práce zaměřuje na přehled strukturálních fondů a způsob financování. Práce také nabízí přehled legislativy a omezení, které doprovází žadatele při všech fázích projektu. Nedílnou součástí práce je i analýza prostředí v České republice týkající se financování ekologických investic. Praktická část ukazuje, zda je ekologická investice pro investora zajímává a hlavně přínosná. K tomuto by měla posloužit Cost Benefit Analýza.

This diploma thesis focuses on financing of ecological investments, let us say financing of alternative sources of energy, especially fotovoltaic eletric power stations. In one part the thesis focuses on the list of structural funds and ways of financing. The thesis offers the abstract of legislation and limitations which goes with the applicants in all periods of projects. The analysis of the background concerning the financing ecological investments in the Czech Republic is the integral part of thesis. The practical part of the thesis shows if the ecological project could be interesting and beneficial for investors. The Cost Benefit Analysis could be instrumental for finding out the relevant information.
Financing of Ecological Investments with the Support of Structural Funds of EU
Keywords: Finanční analýza; investice; formy financování; zhodnocení investic; dotace; regionální politika; strukturální fondy; programovací období 2007 – 2013; operační programy; Cost Benefit Analýza; externality; Financial analysis; investment; forms of financing; investment evaluation; grant; the European Union; regional policy; Structural funds; programming period 2007-2013; operational programmes; Cost Benefit Analysis; externalits